2016
DOI: 10.1016/j.colsurfa.2016.03.072
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant screening for foam EOR: Correlation between bulk and core-flood experiments

Abstract: Aqueous foams play an important role in many industrial processes, from ore separation by froth flotation to enhanced oil recovery (EOR). In the latter case, the foam is used as a means of increasing the sweep efficiency through the oil bearing rock -the complex, structure dependent, flow behaviour of the foam [Jones et al., 2013] means that it has improved penetration of lower permeability regions than would be obtained with a Newtonian fluid. An understanding of how foam behaves when flowing through a rock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 46 publications
3
57
0
Order By: Relevance
“…In their result (Figure 6), it can be observed that as the concentration of foaming agent increases, the foam height and foam half-life increased considerably, while the surface tension lowered. From the figure, it can also be observed that the IFT values are in direct relationship with the half-life value, hence this clearly supports the findings of Jones et al (2016) above with respect to foam stability. Therefore, the plot of IFT and foam half-life could serve as a method to describe the foam quality and the stability.…”
Section: Eor-foam Half-lifesupporting
confidence: 78%
See 2 more Smart Citations
“…In their result (Figure 6), it can be observed that as the concentration of foaming agent increases, the foam height and foam half-life increased considerably, while the surface tension lowered. From the figure, it can also be observed that the IFT values are in direct relationship with the half-life value, hence this clearly supports the findings of Jones et al (2016) above with respect to foam stability. Therefore, the plot of IFT and foam half-life could serve as a method to describe the foam quality and the stability.…”
Section: Eor-foam Half-lifesupporting
confidence: 78%
“…The work of Jones et al (2016) described the relationship between the foam half-life and IFT to measure the foam stability. They found that, foam stability assessment could not be established from the plot of foam half-life against the IFT in the absence of oil.…”
Section: Eor-foam Half-lifementioning
confidence: 99%
See 1 more Smart Citation
“…Although both mechanisms are within the mechanism of capillary pressure, capillary adsorption utterly depends on the surfactant formulation in comparison to the capillary snap-off. Two-dimensional presentation of foam system are being graphically depicted in Figure 1 (Jones et al, 2016a(Jones et al, , 2016bKapetas et al, 2016Kapetas et al, , 2017Khoshnevis et al, 2017;Li et al, 2006;Razmjoo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This diffusion causes the coarsening of bubble sizes with time as the smaller bubbles gradually coalesce into larger bubbles. Finally, the foam becomes dry and takes polyhedral structure (Jones et al 2016). Recently, the coarsening behavior has been investigated in porous media by Jones (2018) at both pores and core scales using micromodel and sandstone core.…”
Section: Introductionmentioning
confidence: 99%